A variant in the promoter of MBL2 is associated with protection against visceral leishmaniasis in Morocco - Hamdi, Salsabil; Ejghal, Rajaa; Idrissi, Mouna; Ezzikouri, Sayeh; Hida, Mohammed; Soong, Lynn; Amarouch, Hamid; Lemrani, Meryem (Infection, genetics and evolution, 2013)
► We investigated the impact of MBL2 polymorphisms on susceptibility to VL in Moroccan children. ► We analyzed MBL2 polymorphisms at exon1 codons 52, 54, 57 and at –221 promoter region. ► We genotyped 112 cases with VL, 97 asymptomatic subjects and 42 uninfected individuals. ► No significant association between polymorphisms in exon1 and outcome of infection. ► The MBL2 polymorphism at the -221 promoter region plays a protective role in L. infantum infection. Progressive visceral leishmaniasis (VL) is fatal if not treated; yet, most infections with the causative agents are asymptomatic. We hypothesized that genetic factors contribute to this variable response to infection. The mannose-binding lectin 2 gene (MBL2) is a candidate that merits examination in the context of VL because it enhances infection with intracellular pathogens. Four functional MBL2 polymorphisms at codons 52, 54, 57 and in the promoter at the -221 position (X/Y) are known to be associated with the outcome of several diseases. The aim of the present study was to investigate whether these functional variants were associated with VL in Moroccan children. Here, we genotyped polymorphisms by sequencing and PCR-RFLP in 112 individuals with VL, 97 asymptomatic subjects and 42 healthy individuals who had no evidence of present or past infection. Regression analysis showed no significant association between polymorphisms in exon 1 genotypes and outcome of infection with Leishmania infantum. However, the genotype XY in −221 conferred a protective role against VL in our study population with a significant difference (OR=0.291; CI [0.158–0.538]; p=0.0006). Subjects with YY genotypes in -221 had a higher risk to developing VL. We concluded that MBL2 polymorphism at the -221 promoter region plays a protective role in L. infantum infection.